Uso do Índice de Qualidade da Dieta Infantil Revisado para avaliar a dieta alimentar de pré-escolares, seus preditores sociodemográficos e sua associação com peso corporal Use of the Revised Children's Diet Quality Index to assess preschooler's diet quality, its sociodemographic predictors, and its association with body weight status - Sibylle Kranz; Jill L. Findeis; Sundar S. Shrestha (Elsevier, 2008)
OBJETIVO: Determinar o nível de qualidade global da dieta, preditores sociodemográficos de qualidade da dieta e a associação entre qualidade da dieta e peso corporal em uma amostra nacionalmente representativa de pré-escolares. MÉTODOS: Estudo transversal utilizando uma amostra de crianças de 2 a 5 anos com dados sociodemográficos, alimentares e antropométricos (n = 1.521) do National Health and Examination Survey 1999-2002. A qualidade global da dieta foi determinada através do Índice de Qualidade da Dieta Infantil Revisado. Preditores sociodemográficos (idade, sexo, grupo sociodemográfico e étnico, renda domiciliar, freqüência escolar, participação em programa federal de alimentação) de qualidade da dieta foram determinados através de modelos de regressão linear múltipla na amostra total e estratificados por renda domiciliar para aquelas elegíveis no programa Food Stamp (< 1,3 da razão pobreza/renda) ou no Special Supplemental Program for Women, Infants, and Children (razão pobreza/renda < 1,85). A associação entre qualidade da dieta e a prevalência de obesidade infantil foi avaliada através dos testes de qui-quadrado de Pearson. Significância estatística foi estabelecida em p £ 0,05. Toda a análise foi conduzida por meio de rotinas complexas de delineamento da pesquisa. RESULTADOS: Em média, os pré-escolares consumiram níveis sub-ótimos de grãos integrais, frutas, vegetais e laticínios. A qualidade global da dieta diminuiu proporcionalmente ao aumento de idade (coeficiente beta: -2,38, p < 0,001), mas melhorou proporcionalmente ao aumento de renda domiciliar na amostra integral (coeficiente beta: 1,22, p < 0,001), mas não nas sub-populações de baixa renda. Crianças méxico-americanas apresentaram melhor qualidade de dieta do que crianças brancas não-hispânicas (coeficiente de beta: 2,18, p < 0,033), principalmente no grupo de baixa renda (coeficiente de beta: 3,57, p < 0,006). A prevalência de obesidade infantil diminuiu significativamente com o aumento da qualidade da dieta. CONCLUSÕES: A qualidade da dieta de pré-escolares precisa ser melhorada para dar apoio à prevenção de obesidade infantil nas fases iniciais da vida. OBJECTIVE: To determine the level of overall diet quality, sociodemographic predictors of diet quality, and the association between diet quality and body weight status in a nationally representative sample of preschoolers. METHODS: Cross-sectional study using a sample of 2-5 years old with sociodemographic, dietary, and anthropometric data (n = 1,521) in the National Health and Examination Survey 1999-2002. Overall diet quality was determined using the Revised Children's Diet Quality Index. Sociodemographic predictors (age, sex, sociodemographic, ethnic group, household income, preschool attendance, federal food program participation) of diet quality were determined using multiple linear regression models in the total sample and stratified by household income for Food Stamp eligible (< 1.3 of the poverty income ratio) or Special Supplemental Program for Women, Infants, and Children eligible (poverty income ratio < 1.85). Association between diet quality and prevalence of childhood obesity was assessed with Pearson chi-square tests. Statistical significance was assumed at p £ 0.05. All analysis was conducted using complex survey design routines. RESULTS: On average, preschooler consumed suboptimal levels of whole grains, fruits, vegetables, and dairy. Overall diet quality decreased with increasing age (beta-coefficient: -2.38, p < 0.001) but improved with increasing family income in the full sample (beta-coefficient: 1.22, p < 0.001) but not in the low-income subpopulations. Mexican American children had significantly better diet quality than non-Hispanic white children (beta-coefficient: 2.18, p < 0.033) especially in the low income group (beta-coefficient: 3.57, p < 0.006). Childhood obesity prevalence decreased significantly with increasing diet quality. CONCLUSIONS: Preschooler's diet quality needs to be improved to support the prevention of childhood obesity early in life.